Remittances, Consumption and Investment in Ghana - Adams, Richard H., Jr. (World Bank, Washington, DC, 2012)
This paper uses a new, nationally-representative household survey from Ghana to analyze within a rigorous econometric framework how the receipt of internal remittances (from within Ghana) and international remittances (from African or other countries) affects the marginal spending behavior of households on a broad range of consumption and investment goods, including food, education and housing. Contrary to other studies, which find that remittances are spent disproportionately on consumption (food and consumer goods/durables) or investment goods (education and housing), the findings show that households receiving remittances in Ghana do not spend more at the margin on food, education and housing than households with similar income levels and characteristics that do not receive remittances. When the analysis controls for endogeneity and selection bias, the findings show that any differences in the marginal spending behavior between remittance-receiving and non-receiving households are explained completely by the observed and unobserved characteristics of households. Households in Ghana treat remittances just like any other source of income, and there are no changes in marginal spending patterns for households with the receipt of remittance income.